Joint optimisation of transmit beamspace and receive filter in frequency diversity array‐multi‐input multi‐output radar. Issue 12 (1st October 2022) - Zhou, Changlin; Wang, Chunyang; Gong, Jian; Tan, Ming; Bao, Lei; Liu, Mingjie
Abstract: Frequency diversity array (FDA) radar provides more degrees of freedom and can generate range‐angle‐time‐dependent beampattern. Furthermore, based on the receiver's multi‐input multi‐output (MIMO) scheme, the frequency diversity array‐multi‐input multi‐output (FDA‐MIMO) radar can develop a range‐dependent but time‐independent beampattern. Taking advantage of this feature, this article improves the signal‐to‐interference‐plus‐noise ratio and the effective suppression of interference by jointly optimising the transmit beamspace and the receive filter. Since the optimisation problem is a non‐convex problem with constant energy constraints, we transform it into two convex subproblems with restrictions. The whole algorithm follows the alternate optimisation over receive filter and transmit beamspace. By simulating challenging scenarios, we confirmed the effectiveness and superiority of the method.